A crossover control study of three methods of heat acclimation on the magnitude and kinetics of adaptation - Kissling, L. S.; Akerman, A. P.; Campbell, H. A.; Prout, J. R.; Gibbons, T. D.; Thomas, K. N.; Cotter, J. D. (Experimental Physiology, 2022)
Heat acclimation (HA) can improve heat tolerance and cardiovascular health. The mode of HA potentially impacts the magnitude and time course of adaptations, but almost no comparative data exist. We therefore investigated adaptive responses to three common modes of HA, particularly with respect to plasma volume. Within a crossover repeated-measures design, 13 physically-active participants (5 female) undertook four, 5-d HA regimes (60 min/d) in randomised order, separated by =4 wk. Rectal temperature (Tre) was clamped at neutrality via 36.6C (thermoneutral) water immersion (TWI; i.e., control condition), or raised by 1.5°C via heat stress in 40°C water (HWI), Sauna (55°C, 52% RH), or exercise in humid heat (40°C, 52% RH; ExH). Adaptation magnitude was assessed as the pooled response across days 4 to 6, while kinetics was assessed via the 6-d time series. Plasma volume expansion was similar in all heated conditions but only higher than TWI in ExH (by 4%, p = 0.036). Approximately two thirds of the expansion was attained within the initial 24 h and was moderately related to that present on day 6, regardless of HA mode (r = 0.560-0.887). Expansion was mediated by conservation of both sodium and albumin content, with little evidence for these having differential roles between modes (p = 0.706 and 0.320, respectively). Resting Tre decreased by 0.1-0.3°C in all heated conditions, and SBP decreased by 4 mm Hg, but not differentially between conditions (p=0.137). In conclusion, HA mode did not substantially affect the magnitude or rate of adaptation in key resting markers of short-term HA.